ClinOmicsTrail(bc): a visual analytics tool for breast cancer treatment stratification - Schneider, Lara; Kehl, Timo; Thedinga, Kristina; Grammes, Nadja Liddy; Backes, Christina; Mohr, Christopher; Schubert, Benjamin; Lenhof, Kerstin; Gerstner, Nico; Hartkopf, Andreas; Wallwiener, Markus; Kohlbacher, Oliver; et al. (Bioinformatics, 2019)
AbstractMotivation. Breast cancer is the second leading cause of cancer death among women. Tumors, even of the same histopathological subtype, exhibit a high g
Gesehen am 19.05.2020